Effective Strategy to Increase Participation of Local Papuan Communities in The Management And Utilization of Mangroves on Payum Beach Merauke - Sajriawati, Sajriawati; Sianturi, Reny; Nurliah, Nurliah; Sunarni, Sunarni (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2024)
One solution to the problem of mangrove degradation faced by the Payum Beach community is to provide training and assistance in mangrove management and utilization. Community participation in mangrove management can be interpreted as the active involvement of the community in every stage of mangrove area management. The training and assistance program is aimed at the local community of Payum Beach, especially women, with a total of 40 participants interested in the program being carried out. Training is carried out through lectures, discussions, and direct practice, while assistance is carried out to ensure the application of the techniques taught. Mangrove management training is through nurseries and making seed houses, while utilization is through mangrove leaf ecoprint training. The results show that this ecoprint and mangrove nursery training has proven effective in increasing the knowledge and skills of participants in various aspects, with an average increase in percentage above 80%, namely 83%. These results indicate the success of the training in empowering local Papuan communities and providing new insights that can be applied in economic activities and environmental conservation, especially in mangrove nurseries and making ecoprint products.